Wetlands dominated by palms (Arecaceae), emphasis in those in the New World. - Myers, Ronald L. (2013)
It is well known that most forests in humid tropical lowlands are species rich, and the popular view is that most species are represented by only a few individuals. Despite this common understanding of high richness and low species dominance, within humid tropical regions there are extensive forested ecosystems composed by only few species. These nearly monospecific forests usually occupy poorly drained soils and, except for the mangroves, are quite understudied. In this paper, I review the literature and my own field notes on more than three years studying the structure of palm swamps in Caribbean Costa Rica and Florida to describe some of the major vegetation associations in wetlands dominated by palm species in the Neotropical Region, although I also include some information about similar systems in the Old World Tropics. I mention the most abundant species that compose those palm dominated swamps and –whenever possible– describe forest structure, known distribution, and uses.